Beyond The Smoke: Historical and Ethnographic Notes on The Dayak Basap - Manarul Hidayat (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2025)
This article explores the social history and ethnographic realities of the Dayak Basap, an indigenous people group in East Kalimantan, Indonesia, whose presence remains underrepresented in anthropological literature. Drawing on 47 days of fieldwork conducted in 2022 across several villages in Karangan Subdistrict, especially Karangan Seberang Village, the study examines processes of ethnogenesis and ethnic distribution, intersocietal relations, migration pathways, and cultural continuity. It challenges outsider interpretations of the term